Application of Transfer Function in Predicting the Temperature Field of Space Equipment Under Periodic External Heat Flow - Qian, Jing; Sun, Liwei (Frontiers in Energy Research, 2022)
The temperature state of outer space devices is influenced by the heat flow outside the space. Although traditional numerical simulation analysis methods are highly accurate, they are time-consuming and not conducive for researchers to quickly assess the effects of external heat flow variations, and difficult to apply to program optimization codes that require large-scale iterative calculations, or to codes for on-board temperature control chips. This paper presents an analytical algorithm for heat transfer problems: the transfer function method is applied to the thermal control analysis of outer space equipment with a small computational effort and a simple and straightforward computational procedure. It can be applied to the early prediction of internal temperature changes caused by heat flow changes outside the modification of outer space devices, embedded in the optimization code of a design solution, or integrated into the code of an on-board temperature control chip with a very small computational effort. In general, the transfer function method is not suitable for solving the radiation term, while this paper excludes the radiation term from the time delay calculation based on the small time scale of the radiation term, and solves the time delay of the internal temperature relative to the external surface temperature directly, while the amplitude decay of the internal temperature change relative to the external surface temperature fluctuation is solved by the steady-state method based on the long period of the external heat flow change. The practicality of the transfer function method in the design of thermal control of external space devices is evidenced by comparing the computational results with those of commercial software and experimental results.